2016
DOI: 10.1177/0954405416654085
|View full text |Cite
|
Sign up to set email alerts
|

A study on kerf characteristics of hybrid aluminium 7075 metal matrix composites machined using abrasive water jet machining technology

Abstract: Metal matrix composites are difficult to machine in traditional machining methods. Abrasive water jet machining is a state-of-the art technology which enables machining of practically all engineering materials. This article deals with the investigation on optimization of process parameters of abrasive water jet machining of hybrid aluminium 7075 metal matrix composites with 5%, 10% and 15% of TiC and B 4 C (equal amount of each) reinforcement. The kerf characteristics such as kerf top width, kerf angle and sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…The mechanism of abrasive flow machining is similar to erosive wear, and the effect of machining is achieved by the micro-cutting action generated by the collision between particles in the abrasive flow and the workpiece surface. 1720 If the abrasive particle is regarded as a micro-tool, the angle and speed of the micro-tool, when it collides with the workpiece surface under the action of the flow field, are randomly distributed. 21 The horizontal component of the micro-tool force mainly causes the plowing damage to the target, and the vertical component mainly causes the impact damage.…”
Section: Mechanism Of Abrasive Flow Machiningmentioning
confidence: 99%
“…The mechanism of abrasive flow machining is similar to erosive wear, and the effect of machining is achieved by the micro-cutting action generated by the collision between particles in the abrasive flow and the workpiece surface. 1720 If the abrasive particle is regarded as a micro-tool, the angle and speed of the micro-tool, when it collides with the workpiece surface under the action of the flow field, are randomly distributed. 21 The horizontal component of the micro-tool force mainly causes the plowing damage to the target, and the vertical component mainly causes the impact damage.…”
Section: Mechanism Of Abrasive Flow Machiningmentioning
confidence: 99%
“…Under normal conditions, this value is lower, which means that the method of machining materials being discussed may be considered as relatively accurate. Given the above, AWJ, which is a universal technological tool, provides itself with a wider range of machining applications, enabling the shaping of many types of materials, such as metals and its alloys [ 14 , 15 , 16 , 17 , 18 , 19 ], ceramic, glass [ 20 ], composites [ 21 , 22 ], flammable materials, leather, and natural stone-based materials [ 23 ], as well as regenerating the cutting ability of grinding tools [ 24 ]. Nevertheless, there is still a need for further research related to this technology in order to increase the efficiency of material machining.…”
Section: Introductionmentioning
confidence: 99%
“…Under such circumstances, the effective utilization of experimental, modeling, and optimization methodology makes possible a greater improvement in decision-making with new technological solution that can simultaneously satisfy and control the several distinctive as well as contradictory objectives (multi-objective) in order to make the HAJM process as an excellent choice for machining of advanced engineering ceramic and quartz materials. Several statistical and computational approaches such as MRA [1][2][3], RSM [4][5][6][7][8][9], ANN [10][11][12][13] have been applied for predictive modeling and Taguchi method [14][15][16][17][18], GRA [19][20][21][22][23][24][25], desirability function approach of RSM [26][27][28][29][30][31][32], PCA [33,34], TOPSIS [35], GA [11,12,36,37], PSO [38,39] have been employed for parametric as well as process optimization in abrasive jet machining with the help of carrier gas or liquid medium. Extensive studies have been reported by employing various experimental designs, modeling techniques, and optimization approaches in order to assess or investigate th...…”
Section: Introductionmentioning
confidence: 99%